Chinese investment in Africa through the One Belt One Road Initiative (OBOR): the case of Ethiopia, Tanzania and Kenya - Khalema, Hlolohelo (University of the Free State, 2021)
This study uses the case studies of Ethiopia, Kenya and Tanzania to examine China-Africa relations through the One Belt One Road (OBOR) initiative. China-Africa relations have come under the spotlight in recent years and even made news headlines the world over as various stakeholders grapple with the nature of this relationship. Overall, western countries have presented recent Sino-Africa relations as being tilted in favour of the Chinese, who have been at the same time accused of significantly drawing African countries and trapping them in a vicious circle of debt. The study demonstrates that, China has extended and continues to extend huge loans to many African countries though the framework of FOCAC and the OBOR for a number of huge developmental projects linked to infrastructure development as well as technological advancement. A number of factors have pushed African countries to turn to China for loans, mainly because of its hands off approach which is diametrically opposed to the approach used by other bilateral lending institutions such as the World Bank and the International Monetary Fund (IMF) which attach rather stringent pre-conditions, which in some instances call for good governance and democracy. This is one of the main reasons why African leaders have adopted a look east approaching an attempt to avoid western countries superintending over their governance styles. The three east African countries have been chosen as case studies because of their geographic position which is very strategic for the OBOR connection. These countries provide a useful outlet from Africa, for oil and other crucial raw materials needed by China, and this explains why they are recipients of huge loans for the rehabilitation and construction of port facilities, roads and railway lines. The study is qualitative in nature and uses secondary literature, various institutional reports and newspapers to tell the story of China in Africa through the OBOR lens. It contributes to the growing body of literature by specifically focusing on the OBOR initiative in east Africa and demonstrates the benefits and disadvantages of this kind of investment.
Dissertation (M.A. (Centre for Africa Studies))--University of the Free State, 2021
Keywords: China; Africa; Ethopia; Kenya; Tanzania; Foreign policy; Debt; Infrastructure; One Belt One Road; Maritime; Silk Road